IPTEKS SISTEM PENGENDALIAN INTERNAL KAS PADA PT. BURSA EFEK INDONESIA KP PAPUA - Tambunan, Erwin Hasudungan; Runtu, Treesje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Indonesia Stock Exchange (IDX) KP Papua is a government institution that acts as the exchange organizer. This means that the Indonesia Stock Exchange has the task of facilitating securities trading in Indonesia. In addition to trading, the IDX also runs educational activities for the community, every education that is done certainly requires cash for every activity and as we know that cash is the most smooth and easy asset to occur cheating on cash and it is one of the risks in the company and to minimize fraud the company can use internal controls on cash so that fraud can be minimized. Internal control is a way that management can prevent fraud that might occur, based on research conducted on the Indonesia Stock Exchange in Papua, conclusions can be drawn that internal control of cash receipts in the company will run well when the control elements and presentation of financial statements are made with applicable standards.Keywords: Current Assets, Internal Control, Cash Receipt